Mutational characterization of Omicron SARS-CoV-2 lineages circulating in Chhattisgarh, a central state of India - Singh, Pushpendra; Sharma, Kuldeep; Shaw, Dipika; Bhargava, Anudita; Negi, Sanjay Singh (Frontiers in Medicine, 2023)
Introduction: SARS-CoV-2 Omicron variant emergence in India in early 2022 has caused fear of its rapid spread. With no published data from Chhattisgarh (CG), a central state of India, this study was planned to mutationally characterize the Omicron lineages circulating in CG. Material and Methods: Whole genome sequencing (WGS) of SARS-CoV-2 was done in one hundred eight SARS-CoV-2 positive samples referred from various district hospital and AIIMS, Raipur, Chhattisgarh. Results: All 108 SARS-CoV-2 sequences were belonged to Omicron of clade 21L(84%), 22B(11%) and 22D(5%). BA.2 and its sublineages were predominantly found in 93.5% sequences, BA.5.2 and its sublineage BA.5.2.1 in 4.6% and B.1.1.529 in 2% sequences. Among BA.2, the sublineages found were BA.2(38%), BA.2.38(32%), BA.2.75(9.25%), BA.2.56, BA.2.76 and BA.5.2.1(5% each), BA.2.74(4.6%), BA.5.2.1(3.7%), BA.2.43 and B.1.1529(1.8% each) and BA.5.2(0.9%). Maximum mutations were noticed in Spike (46), followed by nucleocapsid (5), Membrane (3) and Envelope (2) genes respectively. Other mutations were detected in ORF1a (13) followed by ORF1b (6), ORF3a (2), ORF6 and ORF8(1 mutation each). These sequences belonged maximum to Omicron clade 21L (84%), followed by 22B (11%) and 22D (5%). Total mutations detected in spike gene of different variants were BA.1.1529 (32), BA.2(44), BA.2.38(37), BA.2.43(38), BA.2.56(30), BA.2.74(31), BA.2.75(37), BA.2.76(32), BA.5.2 and BA.5.2.1(38 similar mutations). Spike gene showed the signature mutations of T19I, V213G in N terminal domain (NTD), S373P, S375F, T376A, D405N in receptor binding domain(RBD), D614G, H655Y, N679K, P681H at furin cleavage site, N764K, D796K in fusion peptide and Q954H and N969K in Heptapeptide repeat sequence(HR)1. Notably, BA.2.43 exhibited a novel mutation of E1202Q in C terminal. Conclusion: BA.2 followed by BA.2.38 were the predominant Omicron lineage circulating in Chhattisgarh. BA.2.75 appears to supersede other Omicron due to its mutational consortium advantage. High infectivity and immunity evasion warrant periodically genomic monitoring of mutational changes and their induced effect on transmission and virulence for effective management of COVID-19.